2012
DOI: 10.5402/2012/639041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing on Optical Properties of ZnO·LiF·B2O3 Glasses

Abstract: The Melt-quench method is used to synthesize zinc fluoroborate glasses with compositions xZnO 5, 10, 15, and 20). Optical characterization was carried out to examine the variation of optical bandgap energy (E g ) and urbach energy (E U ) with respect to the concentration for the samples annealed at different temperatures (300• C, and 400• C). Annealing shows its effect on the samples with the variations in the values of E g and E U . These variations are explained on the basis of formation of different molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It can be observed that E dir and E ind values for heat‐treated glass samples are greater than those obtained for pristine glass samples. This could be attributed to the fact that during annealing BO 3 structural units might be formed, which connect together to form boroxol rings, thereby decreasing NBOs and increasing the optical band gap of the heat‐treated glasses . The formation of BO 3 units could be confirmed from FTIR investigations for the heat‐treated glasses (Section ), which depicts B–O bond vibrations (BO 3 stretching) at 1521‐1558 cm −1 .…”
Section: Resultsmentioning
confidence: 83%
“…It can be observed that E dir and E ind values for heat‐treated glass samples are greater than those obtained for pristine glass samples. This could be attributed to the fact that during annealing BO 3 structural units might be formed, which connect together to form boroxol rings, thereby decreasing NBOs and increasing the optical band gap of the heat‐treated glasses . The formation of BO 3 units could be confirmed from FTIR investigations for the heat‐treated glasses (Section ), which depicts B–O bond vibrations (BO 3 stretching) at 1521‐1558 cm −1 .…”
Section: Resultsmentioning
confidence: 83%
“…The flexible variance in the structures of borate glasses with the addition of LiF has been reported [2]. We have recently reported the study of LiF.B 2 O 3 glasses with concentrations varied by replacing LiF by Bi 2 O 3 [3,4]. ZnO, being a transition metal oxide, exhibits semiconducting properties.…”
Section: Introductionmentioning
confidence: 98%